Profile and Economic Impacts of Agriculture and Natural Resource Industries in the South Region of Florida - Mohammad Rahmani; Alan W. Hodges; W. David Mulkey (EDIS, 2005)
This report provides a profile of agriculture and natural resource industries and an overview of their economic impacts for a ten county region in southern Florida (Figure 1). Additional reports provide similar information for the central, northeast, northwest, and Suwannee River basin areas of the state. The report is based on data from the IMPLANPro database for Florida counties for 2002 and data from the 2002 Census of Agriculture.